Lignin-based polyurethane doped with carbon nanotubes for sensor applications - Faria, Fernando A. C. (2019)
Modified eucalyptus kraft lignin doped with multiwall carbon nanotubes (MWCNTs) was used as a macromonomer in stepgrowth polymerization with tolylene 2,4-diisocyanate terminated poly(propylene glycol) with the aim of producing a conductive copolymer for all-solid-state potentiometric chemical sensor applications. The crosslinked elastomeric polyurethane obtained was characterized by Fourier transform infrared attenuated total reflection spectroscopy, scanning electron microscopy, tunnelling electron microscopy and atomic force microscopy. Doping of lignin-based polyurethane with MWCNTs produced a significant enhancement of its electrical conductivity without deterioration of thermal and viscoelastic properties. The polymer composite displayed a low percolation threshold at an MWCNT concentration of 0.18% (w/w), which was explained by the oriented distribution of MWCNTs along lignin clusters. All lignin-based polyurethanes doped with MWCNTs at concentrations above the percolation threshold are suitable for sensor applications.